2016
DOI: 10.1016/j.cmet.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Human Platelet Lipidome Reveals Cytosolic Phospholipase A2 as a Regulator of Mitochondrial Bioenergetics during Activation

Abstract: SummaryHuman platelets acutely increase mitochondrial energy generation following stimulation. Herein, a lipidomic circuit was uncovered whereby the substrates for this are exclusively provided by cPLA2, including multiple fatty acids and oxidized species that support energy generation via β-oxidation. This indicates that acute lipid membrane remodeling is required to support energetic demands during platelet activation. Phospholipase activity is linked to energy metabolism, revealing cPLA2 as a central regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
174
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(188 citation statements)
references
References 23 publications
(38 reference statements)
12
174
2
Order By: Relevance
“…*P < 0.01. A recent study demonstrated that platelet activation induced by thrombin leads to increased platelet FAO and lipid mobilization through the actions of cytosolic phospholipase A 2 (40). Although our data show upregulated FAO in PH platelets, we did not observe a significant increase in platelet activation markers.…”
Section: Discussioncontrasting
confidence: 56%
“…*P < 0.01. A recent study demonstrated that platelet activation induced by thrombin leads to increased platelet FAO and lipid mobilization through the actions of cytosolic phospholipase A 2 (40). Although our data show upregulated FAO in PH platelets, we did not observe a significant increase in platelet activation markers.…”
Section: Discussioncontrasting
confidence: 56%
“…3). This eicosanoid has been associated with peroxisome deficiency disorders and chronic kidney disease (Mayatepek et al, 1993; Zhang et al, 2016); more recently it was detected in resting human platelets, but not in thrombin activated platelets (Slatter et al, 2016). While leukotriene B4 (LTB4) is an inflammatory molecule and chemoattractant that mediates the migration of neutrophils induced by heme (Monteiro et al, 2011), omega-oxidation is the main pathway used by human neutrophils to catabolize LTB4, regulating the inflammatory profiles of these cells (Shak and Goldstein, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Protein-lipid interactions vary in specificity, with some protein structures requiring specific cardiolipins [24]. The recent study of human platelet lipidomics showed that mitochondrial lipidome is changed acutely in association with phospholipase and COX-1-dependent increased energy metabolism upon platelet activation [25], supporting the critical role for mitochondrial protein-lipid networks in controlling inflammation. Informative relationships of proteins, lipids and other macromolecules can be visualized with such an approach.…”
Section: Mitochondrial Network and The Redox Codementioning
confidence: 99%